Introduction to operations research / Frederick S. Hillier, Gerald J. Lieberman. - Hillier, Frederick S.; Lieberman, Gerald J. (McGraw Hill, 2024)
This operations research text incorporates a wealth of state-of-the-art, user-friendly software and more coverage of modern operations research topics. This edition features the latest developments in operations research.